An adenovirus traffic update: from receptor engagement to the nuclear pore. (February 2011) - Henaff, Daniel; Salinas, Sara; Kremer, Eric J
Adenoviruses have a bipolar nature: they are ubiquitous pathogens that occasionally cause life-threatening diseases or they can be engineered into powerful gene transfer vectors. The goal of this article is to summarize the most recent advances in adenovirus receptor engagement, internalization, endosomal maturation, endosomal escape and trafficking to the nuclear pore. A better understanding of this initial part of the adenovirus lifecycle may identify new mechanistic-based treatments for adenovirus-induced diseases and help in the engineering of more efficient vectors.